Assessment and analysis of the sensitivity of different methods for estimating of the reference crop evapotranspiration in a cold and moderate climate (Case study: Saqez catchment) - Najmeh Daneshvar-Marvast; Somayeh Soltani-Gerdefaramarzi; Samaneh Poormohammadi (تحقیقات کاربردی علوم جغرافیایی)
The phenomenon of evapotranspiration causes water and moisture losses from water, soil and vegetation levels. Due to the small amount of atmospheric precipitation and water resource constraints in Iran, it is important to calculate it through a suitable method. The present research attempts to evaluate the evapotranspiration reference crop (ETo) and present it in the form of zoning map as a basic tool for water management. In this study, the long-term average of seven meteorological stations and evaporation pan data were used to determine the appropriate ETo estimation method. Evapotranspiration of reference crop was calculated to 14 methods the based on climatic information in each station. Computational methods including combinational methods Penman-based, radiation-temperature method, temperature method and radiation method. The most appropriate computational method was selected based on the R2 and Nash -Sutcliffe statistics. The zoning of evapotranspiration of reference crop was carried out based on the geographic information of the meteorological stations and the GIS software. The results of the research indicate that the best method for this region as the cold and moderate climate are FAO radiation and Blaney-Criddle. Also, the zoning result shows that west of the catchment has less evapotranspiration rather than its east. Sunshine hours, maximum temperature and wind speed were the most effective factors for evapotranspiration in this area by sensitivity analysis.